Reflection of religiosity and spirituality in home interiors of Filipino visual artists - Javier, Maria Jaymee Manuel; Mayo Adelaida Villaraza (2006.)
This study explored the persistence of religiosity and spirituality in Filipino homes in the contemporary setting. Accomplished Filipino visual artists were the target homeowners for this investigation and were the main respondents of this study. Noted for their artistic inclination, artists have their own ways of manifesting their personal interpretation and expression of their religion and spiritual beliefs through the vehicle of art, be it in painting, sculpture, or other media. They also have the passion for appreciating and collecting antiques and artifacts that may convey religious or folk beliefs either found valuable and beneficial for their spiritual growth or simply because they are beautiful and perfect for display. This study also looked at how time has changed or maintained the meaning of religious images and spiritual icons found in homes and how all of these affect the family and the individuals as homeowners. The case study results showed many accessories and artworks, including paintings, sculptures, crafts and heirlooms present inside the respondents' homes. The researcher took photo documentation of these items and their orientation in their respective areas as reflected in the results and discussions of this study. Consequently, qualitative analysis was applied in interpreting the results. The author employed observation and interviews as key elements in satisfying curiosity, providing information and answers to area of inquiry, and at the same time, contributing relevant findings to the study of Interior Design in the Philippines.
Thesis (BID)--University of the Philippines Diliman
Keywords: Dwellings -- Interior decoration -- Religious aspects